Characterization and comparative evaluation of wound healing potential of Ajugarin I and Ajuga bracteosa Wall. ex Benth - Wasti, Yusra; Muntaqua, Durdana; Majid, Muhammad; Naz, Iffat; Zafar, Aroosa; Khan, Safir Ullah; Kazmi, Syeda Tayyaba Batool; Rehman, Tofeeq Ur; Irshad, Nadeem; Fatima, Humaira (Frontiers in Chemistry, 2024)
Ajuga bracteosa (family: Lamiaceae) commonly known as kauri booti, is an important ethnomedicinal plant. The current research was conducted to appraise and compare the in vitro antioxidant and antibacterial as well as in vivo wound healing potentials of Ajugarin I and A. bracteosa extract. Ajugarin I and polyphenols in A. bracteosa were enumerated by reverse-phase high-performance liquid chromatography analysis that confirmed significant amounts of Ajugarin I (2.2±0.02 µg/mg DW) and other phenolic compounds (14 out of 17 standards). A. bracteosa (374.4±0.20 µg AAE/mg of DW, 201.9±0.20 µg AAE/mg of DW, 87±0.30%) showed higher antioxidant profile as compared to Ajugarin I (221.8±0.50 µg AAE/mg of DW, 51.8±0.40 µg This is a provisional file, not the final typeset article AAE/mg of DW, 27.65±0.80%) with 1.86-, 3.89-and 3.15-folds greater activity in ferric reducing antioxidant power, total antioxidant capacity, and free radical scavenging assays, respectively. Likewise, A. bracteosa showed antibacterial activity against 3/5 strains (MIC 25-200 µg/ml) than Ajugarin I (2/5 strains; MIC 50-200 µg/ml). Hemolytic (<2% hemolysis) and dermal toxicity tests rendered both samples non-toxic. Additionally, A. bracteosa (100±2.34% at day 12; 9.33±0.47 days) demonstrated 1.11-and 1.24 folds higher percent wound contraction and epithelization time, respectively than Ajugarin I (95.6±1.52% at day 12; 11.6±0.47 days) as assessed by excision wound model in mice. Histopathological examination further reinforced the better wound healing potential of A. bracteosa with good epithelization, collagen synthesis, fibroblast proliferation and revascularization. Briefly, we endorsed significant comparative antioxidant, antibacterial and wound healing activities of A. bracteosa and Ajugarin I and present these as prospective candidates for wound healing drugs.